Known and Unknown Toxic Substances in New-Generation Tobacco Products - Mercan, Selda; Genc, Merve Kuloglu (Addicta: The Turkish Journal on Addictions, 2023)
In recent decades, new-generation tobacco and nicotine products (NGPs) have been marketed to replace conventional cigarettes because of their health risks all over the world, despite their earlier marketing and production. However, studies indicated that NGPs also have some akin harmful effects besides unknown and undetermined ones. Toxic substances coming from tobacco plants or the heating process make these products dangerous as well as hazardous agents. In this study, toxic substances and ingredients involved in electronic cigarettes and heated and smokeless tobacco products were reviewed, and their prevalence, quantities, and toxic effects were evaluated. Nicotine, tobacco-specific nitrosamines, volatile organic compounds, and some previously identified heavy metals are the prominent toxic substances involved in both conventional and new-generation tobacco products. However, studies conducted on e-cigarettes and heated and smokeless products showed that propylene glycol, glycerol, flavoring agents, and unexpected substances such as illicit or licit drugs, rare metals, and heating-based toxic chemicals are only the tip of the iceberg. Although NPGs are intended to be consumed instead of conventional cigarettes, the number of dual users is substantial, and the long-term effects of these products have not been clarified yet.
Keywords: Aerosol; electronic liquid; heavy metals; humectants; nitrosamines; toxicity